DUE TO THE LEGAL UNDERSTANDING OF PRIVATE Universities IN THE SHADOW OF DIFFERENT FOUNDATIONS (STUDY OF UNIVERSATION OF HEALTHY SOLAR AKBID INTO DR SOETOMO UNIVERSITY SURABAYA) - Bachrul Amiq; M. Yustino Aribawa; Sri Astutik (Awang Long Law Review, 2022)
The large number of private universities in Indonesia creates a quality gap. The unification of private universities is a solution to improve the quality of private higher education. One of the successful ones is the Surya Sehat Midwifery Academy Surabaya with Dr Soetomo University Surabaya. However, the unification process still needs to be examined more deeply about the basic considerations for the unification between the two private universities and the legal consequences of the unification. The unification of the Surya Sehat Midwifery Academy with Dr Soetomo University resulted in the loss of the Surya Sehat Midwifery Academy in the higher education database and merged into Dr Soetomo University into a midwifery study program at the health sciences faculty. which is quite long, namely three years, causing legal uncertainty in the field. This should not need to happen if the government, in this case the Ministry of Education and Culture, applies a Standard Operating Procedure (SOP) for licensing and furthermore to avoid service barriers for alumni of the Surya Sehat Midwifery Academy Surabaya, it is necessary to include alumni data in the health sciences faculty database so that it is physically integrated. as well as virtually.